(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper endeavors to demarcate as well as summarize the most important issues as well as the critical explorations for the realization of the Aravind Adiga’s The White Tiger, Kiran Desai’s The Inheritance of Loss and Arundhati Roy’s The God of Small Things. Adiga recreates the India of Light and the India of Darkness, but the novel is about those nuances and paradoxical points where the two meet and overlap. Though the novel presents a picture of India having an extreme divide between the rich and the poor, The White Tiger, says Adiga, is ‘not a social commentary.’ Kiran Desai touches international issues like Globalization, Multiculturalism, Economic Inequality, Terrorism, Violence, problem of Shadow Immigrants in her award winning book. The Inheritance of Loss is sketched as a double edged sword.